Invasive Pneumococcal Disease burden and PCV coverage in children under five in Southeast Asia: implications for India - Kolhapure, Shafi; Yewale, Vijay; Agrawal, Ashish; Krishnappa, Pradyumna; Soumahoro, Lamine (The Journal of Infection in Developing Countries, 2021)
Introduction: Pneumococcal diseases, though preventable, are a major public health problem in Southeast Asia and particularly in India. Pneumococcal conjugate vaccines (PCVs) are used in the region for over a decade, but to understand their impact, invasive pneumococcal diseases (IPD) burden and PCV coverage data in the region are needed. Methodology: A literature search was conducted to identify i) key evidence published between February 2008 and February 2018 on IPD burden, serotype prevalence and antibiotic resistance in Southeast Asia, and ii) PCV serotype and vaccination coverage in Southeast Asia. Results: 49 relevant articles were included in the final analysis. Mortality in children under 5 years remains high in Southeast Asian countries, with around 25% of deaths due to IPD in India and Pakistan. There was a lack of recent data on IPD incidence. Antibiotic resistance to IPD isolates is increasing, with high resistance rates especially for meningeal isolates. Based on serotype distribution data, primarily for India, available PCVs would cover around 70-80% of IPD-causing serotypes. Vaccine coverage was around 15-20% in India to 98% in South Korea. Conclusions: Widespread PCV use could successfully reduce IPD burden in the region due to high serotype coverage by available PCVs; emphasis should be placed on increasing vaccination uptake, for every child, particularly in India. Reducing health system barriers and improving surveillance and awareness is essential to improve coverage and effectively prevent IPD morbidity and mortality particularly in at risk regions.